The Role of Homework in Teaching English - Zulfizar Qo'chqorova; Akramova Gulhayo (Journal of Innovation in Education and Social Research, 2023)
In this article, the place and role of homework in teaching English, the advantages and disadvantages of homework will be highlighted.